Treatment compliance and quality of life in hemodialysis patients: A cross-sectional study highlighting the ceiling effect in a high-adherence population - Melva Epy Mardiana Manurung; Parulian Dormaida Gultom; Tumpal Manurung; Baharuddin J. E. A. Togatorop; Agustina Sonatha Rumahorbo (KHD-Production, 2026)
Treatment compliance is widely considered important for maintaining patient well-being, although although quality of life may be influenced by factors beyond consistently high treatment compliance. This study investigated the association between treatment compliance and quality of life among patients with chronic kidney disease receiving maintenance hemodialysis in a secondary hospital setting in Indonesia. A cross-sectional study was conducted involving 56 patients recruited consecutively from the hemodialysis unit of Djasamen Saragih Regional Hospital, North Sumatra. Treatment compliance was evaluated using the End Stage Renal Disease Adherence Questionnaire (ESRD-AQ), while The Kidney Disease Quality of Life Short Form (KDQOL-SF) was used to evaluate patient quality of life. Because the variables were not normally distributed, data analysis was performed using Spearman’s rank correlation. Most participants demonstrated high treatment compliance (94.6%), while quality of life was predominantly moderate (83.9%). No statistically significant association was identified between treatment compliance and quality of life (rs = 0.073, 95% CI −0.19 to 0.33, p = 0.611), indicating a negligible association despite high compliance levels. This finding may be explained by a ceiling effect resulting from uniformly high compliance. These findings suggest that psychosocial and contextual influences may play a larger role in determining quality of life than treatment compliance alone. Therefore, improving patient well-being may require nursing strategies that address psychosocial conditions as well as treatment compliance